Free‐running 4D whole‐heart self‐navigated golden angle MRI: Initial results. Issue 5 (5th November 2014) - Coppo, Simone; Piccini, Davide; Bonanno, Gabriele; Chaptinel, Jérôme; Vincenti, Gabriella; Feliciano, Hélène; van Heeswijk, Ruud B.; Schwitter, Juerg; Stuber, Matthias
<x xml:space="preserve">Abstract</x> Purpose To test the hypothesis that both coronary anatomy and ventricular function can be assessed simultaneously using a single four‐dimensional (4D) acquisition. Methods A free‐running 4D whole‐heart self‐navigated acquisition incorporating a golden angle radial trajectory was implemented and tested in vivo in nine healthy adult human subjects. Coronary magnetic resonance angiography (MRA) datasets with retrospective selection of acquisition window width and position were extracted and quantitatively compared with baseline self‐navigated electrocardiography (ECG) ‐triggered coronary MRA. From the 4D datasets, the left‐ventricular end‐systolic, end‐diastolic volumes (ESV & EDV) and ejection fraction (EF) were computed and compared with values obtained from conventional 2D cine images. Results The 4D datasets enabled dynamic assessment of the whole heart with isotropic spatial resolution of 1.15 mm3. Coronary artery image quality was very similar to that of the ECG‐triggered baseline scan despite some SNR penalty. A good agreement between 4D and 2D cine imaging was found for EDV, ESV, and EF. Conclusion The hypothesis that both coronary anatomy and ventricular function can be assessed simultaneously in vivo has been tested positive. Retrospective and flexible acquisition window selection allows to best visualize each coronary segment at its individual time point of quiescence. Magn Reson Med 74:1306–1316, 2015. © 2014 Wiley Periodicals, Inc.